CBIO-13. THOC1 DRIVES GBM AGGRESSION THROUGH MODULATION OF R-LOOPS AND GENOMIC STABILITY. (12th November 2021) - Budhiraja, Shreya; Baisiwala, Shivani; Nandoliya, Khizar; Chen, Li; Dmello, Crismita; Perrault, Ella; Park, Cheol; Zolp, Andrew; Dara, Gabriel; Sonabend, Adam; Ahmed, Atique
Abstract: Glioblastoma (GBM) is the most aggressive and common type of adult malignant brain tumor, with a median survival of only 21 months. To identify which genes drive its highly aggressive phenotype, we performed a genome-wide CRISPR-Cas9 knockout screen. Results showed substantial enrichment of ~160 novel essential oncogenic driver genes and pathways, including a previously unstudied gene THOC1—involved in RNA processing—that showed significant elevations in expression at RNA and protein levels (p< 0.05 ) in GBM, as well as a significant survival benefit in patient datasets when downregulated (p< 0.05 ). Knocking out THOC1 resulted in cell death in multiple GBM patient-derived xenograft (PDX) lines and extended survival compared to the controls (p< 0.01) in vivo . Overexpression of THOC1 in neural stem cells resulted in transformation to a cancerous phenotype, as evidenced by sphere formation in a soft agar assay (p< 0.01 ) and in vivo tumor engraftment assays. Further investigation of THOC1 through immunoprecipitation in neural stem cells and multiple GBM lines showed significant interaction in GBM with histone deacetylase complex SIN3A, involved in recruiting major histone deacetylases in order to close the DNA and prevent the accumulation of R-loops, RNA:DNA hybrids that pose a threat to genomic stability. Additional investigation revealed that THOC1-knockdowns in vitro induced R-loop formation and DNA damage, while THOC1-overexpression in vitro resulted in an untenable decrease in R-loops and DNA damage, suggesting that the THOC1-SIN3A axis is elevated in GBM in order to prevent the accumulation of genotoxic R-loops. Additionally, histone deacetylase activity was shown to be elevated in THOC1-overexpression conditions and reduced in THOC1-knockdown conditions, confirming that the THOC1-SIN3A axis functions to prevent R-loop accumulation through the epigenetic regulation. In summary, our whole-genome CRISPR-Cas9 knockout screen has identified a promising therapeutic target for GBM—a disease desperately in need of therapeutic innovations.